Over-expression of AtPAP2 in Camelina sativa leads to faster plant growth and higher seed yield - Zhang Youjun; Yu Laura; Yung Ka-Fu; Leung Dennis YC; Sun Feng; Lim Boon L (Biotechnology for Biofuels, 2012)
Abstract Background Lipids extracted from seeds of Camelina sativa have been successfully used as a reliable source of aviation biofuels. This biofuel is environmentally friendly because the drought resistance, frost tolerance and low fertilizer requirement of Camelina sativa allow it to grow on marginal lands. Improving the species growth and seed yield by genetic engineering is therefore a target for the biofuels industry. In Arabidopsis, overexpression of purple acid phosphatase 2 encoded by Arabidopsis (AtPAP2) promotes plant growth by modulating carbon metabolism. Overexpression lines bolt earlier and produce 50% more seeds per plant than wild type. In this study, we explored the effects of overexpressing AtPAP2 in Camelina sativa. Results Under controlled environmental conditions, overexpression of AtPAP2 in Camelina sativa resulted in longer hypocotyls, earlier flowering, faster growth rate, higher photosynthetic rate and stomatal conductance, increased seed yield and seed size in comparison with the wild-type line and null-lines. Similar to transgenic Arabidopsis, activity of sucrose phosphate synthase in leaves of transgenic Camelina was also significantly up-regulated. Sucrose produced in photosynthetic tissues supplies the building blocks for cellulose, starch and lipids for growth and fuel for anabolic metabolism. Changes in carbon flow and sink/source activities in transgenic lines may affect floral, architectural, and reproductive traits of plants. Conclusions Lipids extracted from the seeds of Camelina sativa have been used as a major constituent of aviation biofuels. The improved growth rate and seed yield of transgenic Camelina under controlled environmental conditions have the potential to boost oil yield on an area basis in field conditions and thus make Camelina-based biofuels more environmentally friendly and economically attractive.